Ultra‐rare sarcomas: A consensus paper from the Connective Tissue Oncology Society community of experts on the incidence threshold and the list of entities. Issue 16 (28th April 2021) - Stacchiotti, Silvia; Frezza, Anna Maria; Blay, Jean‐Yves; Baldini, Elizabeth H.; Bonvalot, Sylvie; Bovée, Judith V. M. G.; Callegaro, Dario; Casali, Paolo G.; Chiang, RuRu Chun‐ju; Demetri, George D.; Demicco, Elisabeth G.; Desai, Jayesh; et al.
Abstract : Background: Among sarcomas, which are rare cancers, many types are exceedingly rare; however, a definition of ultra‐rare cancers has not been established. The problem of ultra‐rare sarcomas is particularly relevant because they represent unique diseases, and their rarity poses major challenges for diagnosis, understanding disease biology, generating clinical evidence to support new drug development, and achieving formal authorization for novel therapies. Methods: The Connective Tissue Oncology Society promoted a consensus effort in November 2019 to establish how to define ultra‐rare sarcomas through expert consensus and epidemiologic data and to work out a comprehensive list of these diseases. The list of ultra‐rare sarcomas was based on the 2020 World Health Organization classification, The incidence rates were estimated using the Information Network on Rare Cancers (RARECARENet) database and NETSARC (the French Sarcoma Network's clinical‐pathologic registry). Incidence rates were further validated in collaboration with the Asian cancer registries of Japan, Korea, and Taiwan. Results: It was agreed that the best criterion for a definition of ultra‐rare sarcomas would be incidence. Ultra‐rare sarcomas were defined as those with an incidence of approximately ≤1 per 1, 000, 000, to include those entities whose rarity renders them extremely difficult to conduct well powered, prospective clinical studies. On the basis of this threshold, a list of ultra‐rare sarcomas was defined, which comprised 56 soft tissue sarcoma types and 21 bone sarcoma types. conclusions: Altogether, the incidence of ultra‐rare sarcomas accounts for roughly 20% of all soft tissue and bone sarcomas. This confirms that the challenges inherent in ultra‐rare sarcomas affect large numbers of patients. Abstract : The list of ultra‐rare sarcomas, defined as those sarcomas with an incidence ≤1 per 1, 000, 000, comprises 56 soft tissue sarcoma and 21 bone sarcoma types. The incidence of ultra‐rare sarcomas accounts for roughly 20% of all soft tissue and bone sarcomas, confirming that challenges inherent to ultra‐rare sarcomas affect large numbers of patients.